Communicating treatment options to older patients with advanced kidney disease: a conversation analysis study - Lucy E. Selman; Chloe B. Shaw; Ryann Sowden; Fliss E. M. Murtagh; James A. Tulsky; Ruth Parry; Fergus J. Caskey; Rebecca K. Barnes (BMC Nephrology, 2024)
Abstract Background Choosing to have dialysis or conservative kidney management is often challenging for older people with advanced kidney disease. While we know that clinical communication has a major impact on patients’ treatment decision-making, little is known about how this occurs in practice. The OSCAR study (Optimising Staff-Patient Communication in Advanced Renal disease) aimed to identify how clinicians present kidney failure treatment options in consultations with older patients and the implications of this for patient engagement. Methods An observational, multi-method study design was adopted. Outpatient consultations at four UK renal units were video-recorded, and patients completed a post-consultation measure of shared decision-making (SDM-Q-9). Units were sampled according to variable rates of conservative management. Eligible patients were ≥ 65 years old with an eGFR of ≤ 20 mls/min/1.73m2 within the last 6 months. Video-recordings were screened to identify instances where clinicians presented both dialysis and conservative management. These instances were transcribed in fine-grained detail and recurrent practices identified using conversation-analytic methods, an empirical, observational approach to studying language and social interaction. Results 110 outpatient consultations were recorded (105 video, 5 audio only), involving 38 clinicians (doctors and nurses) and 94 patients: mean age 77 (65–97); 61 males/33 females; mean eGFR 15 (range 4–23). There were 21 instances where clinicians presented both dialysis and conservative management. Two main practices were identified: (1) Conservative management and dialysis both presented as the main treatment options; (2) Conservative management presented as a subordinate option to dialysis. The first practice was less commonly used (6 vs. 15 cases), but associated with more opportunities in the conversation for patients to ask questions and share their perspective, through which they tended to evaluate conservative management as an option that was potentially personally relevant. This practice was also associated with significantly higher post-consultation ratings of shared decision-making among patients (SDM-Q-9 median total score 24 vs. 37, p = 0.041). Conclusions Presenting conservative management and dialysis as on an equal footing enables patient to take a more active role in decision-making. Findings should inform clinical communication skills training and education. Clinical trial number No trial number as this is not a clinical trial.